Content validity by expert judgment of an instrument to measure knowledge, attitudes and practices regarding salt consumption in the population of Peru - Torres Malca, Jenny Raquel (2022)
Introduction: Given the high consumption of salt in the population, there is a need to have a validated tool that measures the knowledge, attitudes, and practices of salt consumption (CAP-salt). Objective: To validate the CAP-salt questionnaire. Methods: Psychometric study of content validity through expert judgment. A total of ve physicians from different specialties were counted. To calculate the degree of agreement between the expert judges, Aiken's V was used as the decision criterion to keep an item; a value ≥ 0.7 was considered. Results: To clarify, V values greater than 0.80 were presented, in addition to a variation coefficient of less than 25%; therefore, none of the items was eliminated. Regarding coherence, they presented a coefficient of variation above 20% and V values greater than 0.71, conrming the decision not to exclude any of them. Regarding the relevance of the items, V values higher than 0.90 were also evidenced, and neither did any of them present a value below the critical one. Conclusions: The questionnaire has presented sufficient evidence of content validity in terms of clarity, coherence, and relevance of the items through the analyses mentioned above. For this reason, it should be used to quantify the CAP-salt of different population groups in the country.